Associations between IL‐1RA polymorphisms and small intestinal bacterial overgrowth among patients with irritable bowel syndrome from India. Issue 10 (30th July 2014) - Srivastava, D.; Ghoshal, U.; Mittal, R. D.; Ghoshal, U. C.
Abstract Background Low‐grade inflammation (controlled by pro and anti‐inflammatory molecules), induced by gut microbes in patients with small intestinal bacterial overgrowth (SIBO), may be associated with irritable bowel syndrome (IBS). Polymorphisms of IL‐RA gene (anti‐inflammatory) was evaluated in IBS and healthy subjects (HS); small intestinal mucosal IL‐1α and β levels (pro‐inflammatory) in relation to the presence of SIBO were evaluated in a subset of patients. Methods Two hundred and twenty‐one IBS patients and 273 age‐ and gender‐matched HS were included. Exactly 209 of 221 patients (Rome III) and 273 HS were genotyped (PCR) for IL‐1RA polymorphism. Mucosal IL‐1α and β levels (pg/mg of biopsy) were estimated (ELISA) in 82/221 patients with and without SIBO (≥105 CFU/mL upper gut aspirate bacteria). Key Results Genotype 1/1 (IL‐1RA over‐producer) was less frequent among patients than controls (p = 0.007); genotypes 1/3 (p = 0.012, OR = 3.301, 95% CI = 1.31–8.35) and 2/3 (both under‐producers; p = 0.009, OR = 7.703, 95% CI = 1.66–35.82) were commoner among IBS. Fifteen of 82 (18.3%) patients had SIBO. Levels of IL‐1α and β were higher among patients with SIBO than without (IL‐1α: 35.4 [20.1–66.8] vs 25.5 [4.2–65.3], p < 0.001; IL‐1β: 206.8 [133.5–365.9] vs 93.1 [25.5–197.7], p < 0.001) and those with bloating than without (p = 0.012; p = 0.015). IL‐1β was higher among patients with Bristol stool type 6 than those with type 1–2 (p = 0.002) and type 3–5 (p = 0.007). Conclusions & Inferences Polymorphisms 1/1 (IL‐1RA over‐producer) was infrequent and 1/3 and 2/3 (under‐producers) frequent among IBS. Increased IL‐1α and β levels were associated with SIBO. Increased IL‐1β level was predominantly associated with bloating and loose stools (Bristol type 6).